Social network analysis for the measurement of formal and informal structures - Pascotto, Siomara Maria Pierangeli; Farina, Milton Carlos; Rodrigues, Thaís Helena Perciavali Telmo; Dugo, José Carlos (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346598808 A discussion around the application of the social network analysis methodology has being helped to understand the social dynamic operation of organizations, including governments, which are subject to different management structures that have a high degree of functional hierarchy. This study was developed in a Federal School Institution in Sao Paulo State – Brazil searching to identify the link developed between Institution administrative support staff members and their social networks. The research objective is to establish a comparison between the link data facts with Social Networks Theories which says that the more ties (contacts) exist in an informal group, the more the network promotes an open environment for exchanging knowledge and information. The research looked forward to identify how do the social networks are developed, how common objectives and subjects turns people closely connected, how do the focal points and main contacts emerge from this community and what are their influences in the rest of the group. It was applied social network measurement methodologies, combined with qualitative instrument analysis. As a conclusion, was found that the informal structure has influence over the formal structure providing an environment for exchanging knowledge and information, pointing out that some characters are actually responsible for the dynamic of networks, occupying driver and strategic position that gives them recognition as such by the other agents in the net.